Contention graph based concurrent scheduling algorithm in millimeter wave WPAN - Yibing WANG; Yong NIU; Weiguang DING; Hao WU (Tongxin xuebao)
The directional antennas and beamforming techniques in millimeter wave (mmWave) bands are used to make concurrent transmission between multiple flows become possible.However,higher mutual interference may be caused by concurrent transmission.Therefore,when the time slots were limited and the number of data flows was large,how to schedule the concurrent flows efficiently was solved by proposed algorithm.The contention graph based spatial-time division multiple access (CB-STDMA) concurrent scheduling algorithm guaranteed the quality of service (QoS) of users,and aimed at maximizing the number of flows with their QoS requirements satisfied.It considered the interference between different flows,and a higher priority was given to the flow with fewer time slots requirement.Extensive simulations demonstrated that the proposed CB-STDMA algorithm increased the number of flows with their QoS requirements satisfied and the network throughput by 50% and 20% respectively compared with the existing algorithms.